Replication-Competent Rhabdoviruses with Human Immunodeficiency Virus Type 1 Coats and Green Fluorescent Protein: Entry by a pH-Independent Pathway - Boritz, Eli (American Society for Microbiology, 1999)
We describe a replication-competent, recombinant vesicular stomatitis virus (VSV) in which the gene encoding the single transmembrane glycoprotein (G) was deleted and replaced by an env-G hybrid gene encoding the extracellular and transmembrane domains of a human immunodeficiency virus type 1 (HIV-1) envelope protein fused to the cytoplasmic domain of VSV G. An additional gene encoding a green fluorescent protein was added to permit rapid detection of infection. This novel surrogate virus infected and propagated on cells expressing the HIV receptor CD4 and coreceptor CXCR4. Infection was blocked by SDF-1, the ligand for CXCR4, by antibody to CD4 and by HIV-neutralizing antibody. This virus, unlike VSV, entered cells by a pH-independent pathway and thus supports a pH-independent pathway of HIV entry. Additional recombinants carrying hybrid env-G genes derived from R5 or X4R5 HIV strains also showed the coreceptor specificities of the HIV strains from which they were derived. These surrogate viruses provide a simple and rapid assay for HIV-neutralizing antibodies as well as a rapid screen for molecules that would interfere with any stage of HIV binding or entry. The viruses might also be useful as HIV vaccines. Our results suggest wide applications of other surrogate viruses based on VSV.